KARAKTERISTIK DAN SIKAP KONSUMEN TERHADAP ONLINE SHOPPING - Asep Hermawan (Universitas Trisakti, 2004)
The objective of this paperis to explore literature conceming the differences of consumers' attitude toward online shopping based on demographic characteristics and to identity the reltionship of consumers' perception of the benefits of online shopping and their attitude toward online shopping. The implications for empirical research are provided.